Heavy de novo methylation at symmetrical and non-symmetrical sites is a hallmark of RNA-directed DNA methylation. - Pélissier, T (1999)
Previous analysis of potato spindle tuber viroid (PSTVd) RNA-infected tobacco plants has suggested that an RNA-DNA interaction could trigger de novo methylation of PSTVd transgene sequences. Using the genomic sequencing technique, the methylation pattern associated with the RNA-directed DNA methylation process has been characterized. Three different PSTVd transgene constructs all showed a similar pattern of methylation. Most of the cytosines at symmetrical as well as non-symmetrical positions appeared to be methylated in both DNA strands of the viroid sequences. Heavy methylation was mostly restricted to the viroid cDNA sequences. Flanking DNA regions immediately adjacent to the viroid cDNA displayed a lower but significant level of cytosine methylation. The observation that the heavy methylation was essentially co-extensive with the length of the PSTVd cDNA sequences provided evidence that a direct RNA-DNA interaction can act as a strong and highly specific signal for de novo DNA methylation. These data also confirmed that de novo methylation was not limited to canonical CpG and CpNpG sites, but can also involve all the cytosine residues located in the genomic region where the RNA-DNA interaction takes place.